2018
DOI: 10.1016/j.jsbmb.2017.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and breast cancer: Past and present

Abstract: The presence of the vitamin D receptor in mammary gland and breast cancer has been recognized since the early 1980s, and multiple pre-clinical studies have demonstrated that its ligand 1,25D modulates normal mammary gland development and sensitivity to carcinogenesis. Although studies have characterized many 1,25D responsive targets in normal mammary cells and in breast cancers, validation of relevant targets that regulate cell cycle, apoptosis, autophagy and differentiation, particularly in vivo, has been cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 50 publications
4
61
0
1
Order By: Relevance
“…From a tumor biology point of view, removal of the tumor by surgical resection and chemotherapy may have also resulted in recovery of circulating 25(OH)D 3 levels. Previous studies suggested that regulation of the vitamin D pathway may be altered in breast cancer cells (39,40). For example, more stable CYP24 mRNA profiles, responsible for clearing of the active metabolite 1,25(OH) 2 D, were found in human breast cancer cells as compared to normal human mammary epithelial cells (41).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…From a tumor biology point of view, removal of the tumor by surgical resection and chemotherapy may have also resulted in recovery of circulating 25(OH)D 3 levels. Previous studies suggested that regulation of the vitamin D pathway may be altered in breast cancer cells (39,40). For example, more stable CYP24 mRNA profiles, responsible for clearing of the active metabolite 1,25(OH) 2 D, were found in human breast cancer cells as compared to normal human mammary epithelial cells (41).…”
Section: Discussionmentioning
confidence: 98%
“…For example, more stable CYP24 mRNA profiles, responsible for clearing of the active metabolite 1,25(OH) 2 D, were found in human breast cancer cells as compared to normal human mammary epithelial cells (41). Also (epigenetic) deregulation and altered expression levels of the vitamin D receptor (VDR) gene during breast carcinogenesis have been described (39,40,42,43). Moreover, exogenous 25OHD exposure resulted in local accumulation of 25OHD and the active metabolite 1,25(OH) 2 D in tumor tissue of a breast cancer mouse model (44).…”
Section: Discussionmentioning
confidence: 99%
“…The VDR is expressed in classical vitamin Dā€responsive tissues such as the intestine, skin, bone, and kidney, but also in a number of malignant tumors. Several studies have shown that the VDR is differentially expressed in benign and malignant breast tissue, suggesting a role for the VDR in transcriptional and cellā€cycle regulation, as well as cell differentiation and apoptosis . Thus, the degree of VDR expression in malignant tissues is inversely related to aggressive tumor characteristics, ie, high expression levels are associated with slower cancer progression and longer survival .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the VDR is differentially expressed in benign and malignant breast tissue, suggesting a role for the VDR in transcriptional and cell-cycle regulation, as well as cell differentiation and apoptosis. (20)(21)(22)(23)(24) Thus, the degree of VDR expression in malignant tissues is inversely related to aggressive tumor characteristics, (25,26) ie, high expression levels are associated with slower cancer progression and longer survival. (15,20,27,28) In murine models of breast cancer, overexpression of the VDR reduces the incidence of pulmonary metastases (26) ; conversely, VDR ablation promotes primary tumor growth as well as lung and hepatic metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the signi cance of CYP24A1 expression level as an independent prognostic factor in breast cancer is still a matter of debate [11][12][13]. The mechanisms by which the calcitriol/VDR axis promotes protective actions from breast cancer are numerous [14], though interference with estrogen receptor (ER) signaling and with aromatase enzyme (CYP19A1) activity [15] has been frequently described. Recent studies have reported that calcitriol can inhibit proliferation of ER-negative cell lines [16,17] and have shown that calcitriol induces the expression of functional ERĪ± in such cells, thus suggesting that the growth-suppressive action of calcitriol is not solely mediated through the ER pathway in breast cancer.…”
Section: Introductionmentioning
confidence: 99%